Strengthening Regional Economic Policy for Investment Attraction: Case in Banten Province - Halik, Abdul (Jurnal Bina Praja, 2016)
The purpose of the study is to analyze the condition of economic potential and economic structure of the region,local investment conditions, as well as to propose a policy in order to strengthen regional economic attraction of investment. The study utilizes qualitative method with descriptive explanation. The result of this study is the attraction of foreign investors and domestic investors to invest in Banten Province is still low, despite the adequately supportive (good enough) economic potential and economic structure in the region. Therefore, it is still necessary to strengthen more appropriate regional economic policies to increase the attraction of investment in Banten province, especially the policy of increasing people’s purchasing power (not in the consumptive context).